2023
DOI: 10.29133/yyutbd.1209177
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Fertilizer Applications on Some Morphological Traits in Fresh Bean

Abstract: The study was conducted to determine the morphological changes caused by different fertilizer applications on the fresh bean, in the Göllü Village of Tusba District of Van Province according to the randomized blocks experimental design in 2019 and 2020. Sazova 1949 dwarf bean variety was used as plant material in the study. The field experiment was carried out with 4 replications and 4 different fertilizer applications (chemical, organomineral, cattle, and vermicompost) except for the control. In the study, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The negative effects of salt stress were reported for tomato (Turhan and Șeniz, 2010), for common beans (Kıpçak et al 2019), and wheat (Yılmaz et al, 2022). However, many researchers also reported that the exogenous applications of amino acids were effective in recovering the plant from salt stress or reducing the negative effects (Jannesari et al, 2016;Alp and Şensoy, 2023). Similar to the present study, Sadak et al (2015) examining broad beans and Souri et al (2017) investigating tomato, squash, and bean plants grown in calcareous soils determined that exogenous amino acid treatments stimulated the shoot and root length; shoot fresh weight, root fresh weight, shoot dry weight, root dry weight; the number of leaves, leaf development, and yield.…”
Section: Variation Of Growth Parameters Of Seedlingmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of salt stress were reported for tomato (Turhan and Șeniz, 2010), for common beans (Kıpçak et al 2019), and wheat (Yılmaz et al, 2022). However, many researchers also reported that the exogenous applications of amino acids were effective in recovering the plant from salt stress or reducing the negative effects (Jannesari et al, 2016;Alp and Şensoy, 2023). Similar to the present study, Sadak et al (2015) examining broad beans and Souri et al (2017) investigating tomato, squash, and bean plants grown in calcareous soils determined that exogenous amino acid treatments stimulated the shoot and root length; shoot fresh weight, root fresh weight, shoot dry weight, root dry weight; the number of leaves, leaf development, and yield.…”
Section: Variation Of Growth Parameters Of Seedlingmentioning
confidence: 99%
“…The first option is expensive and difficult, the second option is time-consuming, and the methods obtained cannot guarantee genetically modified products. Therefore, it seems that the most suitable way in agricultural lands having high salinity levels is the third option, which is the exogenous application of biosimultans such as amino acids, hormones, jasmonates, polyamines, and minerals to plants (Bahjat et al, 2022;Alp and Şensoy 2023). Researchers reported that NH4 + in the amino acid structure participated in the structure of organic compounds directly and with less energy and that exogenous amino acid applications were more advantageous in increasing plant yield and stimulating stress resistance (Çakır, 2017;Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%